NATURAL PRODUCTS PHARMACEUTICAL STANDARDIZATION TOWARDS PHYTOPHARMACA FOR INDONESIAN TRADITIONAL MEDICINE DEVELOPMENT: STANDARDISASI FARMASITIKAL BAHAN ALAM MENUJU FITOFARMAKA UNTUK PENGEMBANGAN OBAT TRADISIONAL INDONESIA - Yuslianti, Euis Reni; Bachtiar, Boy M; Suniarti, Dewi Fatma; Sutjiatmo, Afifah B (Dentika: Dental Journal, 2016)
There is a tendency back to nature treatment in Indonesian community because modern/synthetic medicines is expensive and have a various alarming side effects. That is why natural products medicine becomes more popular, aside from mass media promotions. Researches on natural products such as herbal medicine increases along with the desire to get phytofarmaca that can compete with modern medicines. The aims of this literature review are to discuss and provides information on pharmaceutical standardization of natural products toward phytopharmaca for developing Indonesian traditional medicine. Pharmaceutical standardization will strengthen the basic of pharmaceutical science in producing safe, efficacy, and qualify traditional medicine products. The pharmaceutical standardization consists of standardizing simplicial quality, safety, efficacy, and stable formulation of medicines for use in health services.